Effectiveness of using Balanced Scorecard in Management Accounting: Meta-analysis - Bella Suci Novitri; Walla Astianty Putri; Joko Rianto; Eva Anggara Yunita (AKADEMI TEKNIK ADI KARYA, 2024)
This study aims to evaluate the effectiveness of the use of Balanced Scorecard (BSC) in management accounting through a meta-analysis approach. The Balanced Scorecard is a strategic tool used to measure a company's performance from various perspectives, including finance, customers, internal business processes, and learning and growth. This meta-analysis integrates the results of previous research to provide a comprehensive picture of how BSC affects managerial and organizational performance. The results show that the implementation of BSC significantly contributes to increasing management effectiveness, especially in aligning the company's strategy with operational goals, improving the quality of decision-making, and strengthening managerial accountability with an effect size value of 1,042 (high effect size category). Nonetheless, this study also identifies several factors that can affect the successful implementation of BSC, such as organizational culture, management commitment, and information system quality. These findings have important implications for practitioners and academics in evaluating the benefits and challenges of BSC in the context of management accounting.